The Logic of Contingent Work and Overwork - Stormer, Flora (Relations industrielles / Industrial Relations, 2008)
AbstractIn this article, I draw on institutional theory to propose that a macro-societal market logic is shaping our understanding of the workplace trends of contingent work and overwork. This logic, in combination with specific societal changes, affects how workers experience such trends. Yet paradoxically, the market logic can be used to both support and oppose the trends, resulting in a conceptual stalemate. Research implications are discussed.